48,000 years of climate and forest change from a biodiversity hotspot - Bush, M. B.; Silman, M. R.; Urrego, D. H. (Science, 2004)
A continuous 48,000-year-long paleoecological record from Neotropical lower montane forest reveals a consistent forest presence and an ice-age cooling of ∼5° to 9°C. After 30,000 years of compositional stability, a steady turnover of species marks the 8000-year-long transition from ice-age to Holocene conditions. Although the changes were directional, the rates of community change were no different during this transitional period than in the preceding 30,000-year period of community stability. The warming rate of about 1°C per millennium during the Pleistocene-Holocene transition was an order of magnitude less than the projected changes for the 21st century.
id: 1016